Tissue Residues and Pharmacokinetic/Pharmacodynamic Modeling of Tiamulin Against Mycoplasma anatis in Ducks - Elazab, Sara T.; Elshater, Nahla S.; Hashem, Yousreya H.; Park, Seung-Chun; Hsu, Walter H. (Frontiers in Veterinary Science, 2020)
The pharmacokinetics of tiamulin were studied in 2 groups of ducks (n=6) after its oral administration at 2 different doses (30 and 60 mg/kg, respectively). Plasma concentrations of tiamulin were measured by high performance liquid chromatography at different time points up to 24 h post-administration. The maximum plasma concentrations were 0.77 and 2.32 µg/mL attained at 2 h (Tmax) for 30 and 60 mg/kg, respectively. The elimination half-lives for these 2 doses were 3.54 and 6.34 h, respectively. The minimum inhibitory concentration for tiamulin against Mycoplasma anatis (M. anatis) strain 1340 was determined to be 0.06 µg/mL. The proper oral dose of tiamulin against M. anatis in ducks was calculated to be 35 mg/kg/day using the pharmacokinetic/pharmacodynamic modeling. Tiamulin was administered orally (40 mg/kg/day) to 30 ducks for 3 successive days to determine its residues in edible tissues and its preslaughter withdrawal time. The highest tiamulin residues were detected in the liver, followed by the muscle, whereas lower concentrations were detected in the skin and fat. The estimated withdrawal periods of tiamulin were 6, 5, 3, and 3 days for liver, muscle, skin, and fat respectively. Therefore, an oral dosage regimen of 35 mg/kg/day should be adequate for tiamulin against M. anatis. We recommend a preslaughter withdrawal period of 6 days when ducks are treated with 40 mg tiamulin/kg/day, orally, for 3 days.